Hubungan Antara Interaksi Sosial Sesama Rekan Kerja dengan Kinerja Karyawan di Rumah Sakit Umum Daerah (RSUD) Kalisari Batang - Ratna Pratiwi, Anggrainy, Jati Waskito, S.E., M.Si (2016)
The objective of this study was to determine the relationship between sosial interaction with co-workers in hospitals Kalisari employee performance Batang. This study aims to determine the effect of the independent variable on the dependent variable. This study took a sample of 76 employees with engineering sample random sampling of individuals in the population is given an equal opportunity to be sampled in the study. Then do the normality test, multiple linear analysis, T test and F test, test the coefficient of determination (R2). T test research results indicate a significant relationship between sosial interaction with coworkers employee performance. Values obtained t = 4.448 with a significance level of 0.000. By using the 0.05 limit, obtained ttabel 1,992. This means t> t table, which means that Ho refused and Ha accepted